Prevalence and risk factor analysis for HIV/HTLV 1/2 coinfection in Paraíba state, Brazil - Marcela Santos de Souza; Juliana Prado Gonçales; Viviane Martha Santos deMorais; José Valter Joaquim Silva Júnior; Thaísa Regina Rocha Lopes; Joanne Elizabeth Ferraz da Costa; Maria Rosângela Cunha Duarte Côelho (Journal of Infection in Developing Countries)
Introduction: Human T-lymphotropic virus (HTLV) 1 and 2 infections can lead to neurological diseases, mainly in HIV/HTLV 1 coinfected. Furthermore, HTLV 1 infection in HIV/AIDS patients has also been associated with AIDS progression. Despite this, HTLV 1/2 infections are not of mandatory notification in Brazil. Here, we describe the prevalence of HTLV 1/2 in HIV/AIDS patients from Paraíba state, Brazil, as well as the sociodemographic characteristics of the coinfected individuals.